Scientists as Forced Labourers: the Case of Researchers from Kharkiv in the South German Province during World War II - Baumann, Ansbert (Український історичний журнал, 2024)
This article aims to cover a little-known chapter in the history of World War II. In the course of the brutal German occupation rule, not only forced labourers but also scientists were deported from Ukraine to Germany as war booty and forced to work for the Nazi regime. One example of this is mathematicians who arrived in the village of Ummendorf in the Upper Swabia region of southern Germany in the summer of 1943. They were specialists in aerodynamic calculations who had originally come from the Ukrainian Physical-Technical Institute (UPTI) in Kharkiv. In Ummendorf, they came across German colleagues who had been brought there from the city of Aachen, which had been hit by air raids and were deployed there by the Ministry of Aviation for research relevant to the war effort. The researchers from occupied Ukraine also subsequently worked for the Reichsluftwaffe and co-operated with the Gottingen Aerodynamic Research Institute. The research methodology is based on the principle of critical historicisation, which is committed to the principle of the greatest possible objectivity and is based on the analysis of a wide range of sources from German archives and the evaluation of relevant, predominantly Western, research literature. In summary, various conclusions can be drawn from the events described about both the scientific policy of the Nazi state and the social and socio-cultural dynamics of the time. It shows not only the interest of the Nazi regime in the expertise of specialists from occupied Ukraine and the reputation that research work at Ukrainian scientific institutes enjoyed in the racist Nazi state but also the consequences of the everyday coexistence of the scientists with the village population and the difficult situation for the former employees of the Kharkiv’s UPTI after the end of the World War II.